+0  
 
0
215
1
avatar

g(x)=f(x)+p

g(x)=f(x+s)

assuming p and s are the same value

Guest May 16, 2017

Best Answer 

 #1
avatar+7155 
+2

No...for example let's say f(x) = x2

And...if p and s are the same, let's just call them both "p" .

 

First scenario:

g(x) = f(x) + p

g(x) = x2 + p

 

Second scenario:

g(x) = f(x + p)

g(x) = (x + p)2

g(x) = (x + p)(x + p)

g(x) = x2 + 2px + p2

 

f(x) + p  ≠  f(x + p)

 

If f(x) = x, then yes they turn out the same.

But they are not always equal.

hectictar  May 16, 2017
 #1
avatar+7155 
+2
Best Answer

No...for example let's say f(x) = x2

And...if p and s are the same, let's just call them both "p" .

 

First scenario:

g(x) = f(x) + p

g(x) = x2 + p

 

Second scenario:

g(x) = f(x + p)

g(x) = (x + p)2

g(x) = (x + p)(x + p)

g(x) = x2 + 2px + p2

 

f(x) + p  ≠  f(x + p)

 

If f(x) = x, then yes they turn out the same.

But they are not always equal.

hectictar  May 16, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.